Wandering spleen presenting as gastric mass: A rare case (Indian Journal of Case Reports, 2018)
Wandering or ectopic spleen is a rare condition in which spleen is located outside its normal location. Wandering spleen is an incidental finding with a reported incidence of <0.2%, fewer than 500 cases reported worldwide in literature. It presents as a diagnostic challenge as it can easily mimic a neoplastic mass, an abscess, or an organized hematoma. Ultrasonography and contrast tomography are useful radiological methods in the diagnosis of wandering spleen. We report here autopsy case of a 51-year-old male with wandering spleen in gastric wall diagnosed on histopathology but presented as gastric mass mimicking malignancy. This case highlights the importance of radiology and histopathology in the diagnosis of an ectopic spleen. In the absence of spleen on radiology at a normal site and with a presence of intra-abdominal mass, the clinician should keep in mind ectopic spleen as a differential diagnosis.